The Existence of Legal Protection for Female Workers Against Sexual Exploitation Mode 'Staycation' - Selvi Kurniawati; Zahra Putri Maharani Pertiwi; Agus Nurhadi (Fakultas Hukum Universitas Islam Jakarta, 2024)
The term staycation as a connotation of sexual activity in a certain place has become increasingly popular in society, especially after the phenomenon of a viral case in the public. Bosses invited female workers in the company to engage in sexual activities in exchange for certain promises. Female workers are often vulnerable to sexual exploitation in the workplace. This requires legal protection to reduce risks and protect the rights of female workers. This article uses a normative juridical research method with a statutory approach based on various provisions in the TPKS Law and several relevant literatures to analyze aspects of legal protection for female workers. This study finds that the TPKS Law provides an important legal basis to protect women workers from sexual exploitation, including the provision of victims' rights to restitution, handling, recovery, and protection through the Witness and Victim Protection Agency (LPSK). This protection is important to prevent backlash from perpetrators and provide a sense of security to victims. Towards effective implementation of legal protection, socialization and education are needed in an effort to increase legal awareness in the community and reduce the incidence of sexual exploitation in the work environment.